Methods of learning and studying economic sciences - Ortikov, Eldor; Avliyakulov, A; Avazov, A (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Economic theory is inextricably linked with other economicsciences. First, it enriches them with new conclusions by summarizing their achievements. Second, it facilitates their development by arming them with conclusions about general economic theory. Economic theory basically performs three functions: a) understanding of the laws of economics, economic education, economic literacy; b) to serve as a basis for other economic disciplines, to be their theoretical basis; c) to provide practical recommendations on economic policy, to provide a theoretical basis for policy development.